Clinical Application of a Neurosurgical Robot in Intracranial Ommaya Reservoir Implantation - Liu, Huan-Guang; Liu, De-Feng; Zhang, Kai; Meng, Fan-Gang; Yang, An-Chao; Zhang, Jian-Guo (Frontiers in Neurorobotics, 2021)
Background The Ommaya reservoir implantation technique allows for bypass of the blood-brain barrier. It can be continuously administered locally and be used to repeatedly flush the intracranial cavity to achieve the purpose of treatment. Accurate, fast, and minimally invasive placement of the drainage tube is essential during the Ommaya reservoir implantation technique, which can be achieved with the assistance of robots. Methods We retrospectively analyzed a total of 100 patients undergoing Ommaya reservoir implantation, of which 50 were implanted using a robot, and the remaining 50 were implanted using conventional surgical methods. We then compared the data related to surgery between the two groups and calculated the accuracy of the drainage tube of the robot-assisted group. Results The average operation time of robot-assisted surgery groups was 41.17 ± 11.09 min, the bone hole diameter was 4.1 ± 0.5 mm, the intraoperative blood loss was 11.1 ± 3.08 ml, and the average hospitalization time was 3.9 ± 1.2 days. All of the Ommaya reservoirs were successful in one pass, and there were no complications such as infection or incorrect placement of the tube. In the conventional Ommaya reservoir implantation group, the average operation time was 65 ± 14.32 min, the bone hole diameter was 11.3 ± 0.3 mm, the intraoperative blood loss was 19.9 ± 3.98 ml，and the average hospitalization time was 4.1 ± 0.5 days. In the robot-assisted surgery group, the radial error was 2.14 ± 0.99 mm and the axial error was 1.69 ± 1.24 mm. Conclusions Robot-assisted stereotactic Ommaya reservoir implantation is quick, effective, and minimally invasive. The technique effectively negates the inefficiencies of craniotomy and provides a novel treatment for intracranial lesions.